PENGARUH PENGGUNAAN MEDIA INTERAKTIF VIDEO PEMBELAJARAN BERBASIS CANVA PADA MATERI SEJARAH TRADISI ATAU BUDAYA DI INDONESIA TERHADAP KEMAMPUAN KOGNITIF DI SEKOLAH DASAR - Nazhira Yumni Alifah; Destrinelli; Hendra Budiono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of using Canva-based interactive learning videos on the topic of Indonesian traditions and cultural history on elementary school students’ cognitive abilities. The research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of 47 third-grade students of SD Negeri 14/I Sungai Baung, including 24 students in the experimental class and 23 students in the control class. The research instrument was a cognitive ability test measuring remembering (C1), understanding (C2), and applying (C3) levels. Data were analyzed using normality tests, homogeneity tests, and an Independent Sample t-test. The results showed that the posttest mean score of the experimental class (82.29) was higher than that of the control class (68.52). The t-test result indicated a t-value of 6.742 with a significance value of 0.000 (< 0.05), demonstrating a significant effect of Canva-based interactive learning videos on students’ cognitive abilities. The N-Gain score of the experimental class (0.63, moderate category) also indicated better improvement compared to the control class. Therefore, Canva-based learning videos are effective in enhancing elementary school students’ cognitive abilities in learning about Indonesian traditions and cultural history.